The Impact of Corporate Social Responsibility (CSR) Activities on Financial Performance : A European Banking Perspective - Chhabra, Shreyus; Pauknerová, Daniela, 1970-; Schmitt, Judith; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2024)
This thesis explores the complex interplay between Corporate Social Responsibility (CSR) initiatives and the financial performance of European banks. In the context of a changing global banking landscape, where sustainability and ethical responsibilities are gaining prominence, this research employs quantitative methodology to investigate how CSR activities, both directly and indirectly, impact the financial performance of banks in Europe. This study is specifically focused on the European banking sector and aims to test the hypothesis that proactive engagement in CSR can have a significant influence on crucial financial performance indicators such as Return on Assets & Return on Investment. By employing quantitative analysis, this research not only aims to uncover statistical relationships but also aims to determine the strength and direction of these connections. The anticipated outcomes of this study should offer valuable insights for regulatory bodies, and stakeholders. These insights will assist in shaping strategic decision-making processes and contribute to the ongoing discussions surrounding responsible banking practices within the European context.
Vedoucí práce: Daniela Pauknerová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses